Sustained Virological Response Rates to Antiviral Therapy in Genotype 1 and 3 Chronic Hepatitis C Patients: A Study from North India - Gupta, Varun (J Clin Exp Hepatol, 2014)
BACKGROUND: In India, both genotype 3 and 1 are predominant genotypes in patients with chronic hepatitis C (CHC). However, there is scanty data on sustained viral response (SVR) rate with conventionally recommended dual therapy with PEG-IFN and ribavirin. METHODS: In this retrospective study, consecutive patients of CHC of genotypes 1 and 3, attending the single unit of Gastroenterology of our hospital, who received PEG-IFN and ribavirin therapy, were included. Patients who had co-infection with HIV or HBV were excluded. RESULTS: A total of 114 patients were included in the study median age 44 (15–72) years, 79% males. Most common presentation was with chronic hepatitis, while 10 (9%) patients had compensated cirrhosis. Nine (8%) patients had associated diabetes, 16 (14%) patients gave history of significant alcohol abuse. The median baseline HCV RNA level was 3.0 × 10(5) (1.7 × 10(3)–1.8 × 10(7)) IU/mL. The most common genotype was 3 (75%) followed by genotype 1 (25%). 70% patients received PegIFN-α2a (median dose 180 MIU/wk) and 30% patients received PegIFN-α2b (median dose 80 MIU/wk). The median ribavirin dose was 800 (range 800–1200) mg. SVR in genotype 1 was 64% (18/28) while SVR in genotype 3 was 73% (63/86). The factors predicting SVR on univariate analysis were a lower baseline HCV RNA level (less than 3.0 × 10(5)), higher hemoglobin level > 11.8 g/dl, and achievement of rapid virological response (RVR), early virological response (EVR) and end of treatment response (ETR). In multivariate analysis the only baseline factor found independently correlating with SVR was low HCV RNA level (<3.0 × 10(5) IU/mL) (P = 0.003). CONCLUSION: In north India, HCV genotype 3 has a SVR rate of 73%, which is comparable to genotype 1 with SVR rate of 64% when treated with PEG-IFN and ribavirin therapy. A baseline HCV RNA level lower than 3.0 × 10(5) best predicts SVR in addition to achievement of RVR, EVR or ETR.